Multiple Roles of Myd88 in the Immune Response to the Plague F1-V Vaccine and in Protection against an Aerosol Challenge of Yersinia pestis CO92 in Mice - Jennifer L. Dankmeyer; Randy L. Fast; Christopher K. Cote; Patricia L. Worsham; David Fritz; Diana Fisher; Steven J. Kern; Tod Merkel; Carsten J. Kirschning; Kei Amemiya (Journal of Immunology Research)
The current candidate vaccine against Yersinia pestis infection consists of two subunit proteins: the capsule protein or F1 protein and the low calcium response V protein or V-antigen. Little is known of the recognition of the vaccine by the host’s innate immune system and how it affects the acquired immune response to the vaccine. Thus, we vaccinated Toll-like receptor (Tlr) 2, 4, and 2/4-double deficient, as well as signal adaptor protein Myd88-deficient mice. We found that Tlr4 and Myd88 appeared to be required for an optimal immune response to the F1-V vaccine but not Tlr2 when compared to wild-type mice. However, there was a difference between the requirement for Tlr4 and MyD88 in vaccinated animals. When F1-V vaccinated Tlr4 mutant (lipopolysaccharide tolerant) and Myd88-deficient mice were challenged by aerosol with Y. pestis CO92, all but one Tlr4 mutant mice survived the challenge, but no vaccinated Myd88-deficient mice survived the challenge. Spleens from these latter nonsurviving mice showed that Y. pestis was not cleared from the infected mice. Our results suggest that MyD88 appears to be important for both an optimal immune response to F1-V and in protection against a lethal challenge of Y. pestis CO92 in F1-V vaccinated mice.